Intestinal Lymphangiectasia due to Recurrent Giardiasis - Gürol ÖKSÜZOĞLU,; Yusuf BAYRAKTAR,; İbrahim HAZNEDAROĞLU,; Berna GÖKER,; Bedri UZUNALİMOĞLU,; Burhan KAYHAN, (Turkish Journal of Gastroenterology, 2020)
-